The Influence of Knowledge-Oriented Leadership on Innovative Work Behavior in SMEs with Knowledge Sharing as a Mediator - Florentinus Andika Sayang Bati; Dian Ekowati (Eduvest - Journal of Universal Studies, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have been one of the business sectors significantly affected by the changes brought about by Covid-19. Many MSMEs have successfully overcome the challenging period of the Covid-19 pandemic. Particularly, leadership patterns focusing on knowledge, or knowledge-oriented leadership, have emerged as one of the key factors for MSME leaders to develop their businesses. In addition to leadership patterns, MSMEs also emphasize innovative work behavior within the workplace environment, complemented by communication systems focused on knowledge sharing. This study examines the relationship between leadership patterns and knowledge-focused communication towards innovative behavior within the workplace environment. The research involved 600 MSME employees scattered across Indonesia. The study utilized Structural Equation Modeling (SEM) with the assistance of SmartPLS in data management processes. The findings of this study indicate that knowledge-oriented leadership significantly and positively impacts the development of innovative work behavior within the MSME workplace environment. Furthermore, knowledge sharing significantly serves as a mediator for the relationship between knowledge-oriented leadership and the enhancement of innovative work behavior within the MSME workplace environment.